Communicative language teaching in community college: English language lecturers and community college students' perceptions / Nurhazlinda @ Azlin Md Aris - Md Aris, Nurhazlinda @ Azlin (2015)
Communicative Language Teaching (CLT) is significant for teaching and learning of English language. Though quite a number of researches have been done on the implementation of CLT in the world, there is barely any research has been done on Malaysia's Community College. Thus this study aims to address this gap. The aim of this study is to find out the lecturers' and students' perceptions towards CLT in the context of Malaysia's Community College, which is in line with Constructivism theory. For this purpose, a number of data were collected through questionnaire survey and semi-structured interview to two groups of participants: the Community College's lecturers and students respectively. The result of this study indicated that the lecturers and students held relatively positive perceptions towards the implementation of CLT, and perceived communicative based lessons as favourable. This study also hypothesizes that CLT can be feasibly to be taught in the context of Malaysia's Community College in the future. These findings are important as it reflects the future of Malaysia's Community College should the implementation of CLT is done in full scale. The results of this study however are not to be generalized to other tertiary institutions in Malaysia.